Informing professional practice: (future) teachers' choice, use, and evaluation of (non-)scientific sources of educational topics - Thomm, Eva; Seifried, Eva; Bauer, Johannes (Zeitschrift für pädagogische Psychologie, 2021)
. Understanding processes of selecting, evaluating, and using relevant information sources to inform oneself about scientific topics, that is, sourcing, is a current topic within educational psychology. This special issue combines recent research about sourcing with a particular focus on its role in the reception of educational research by (future) teachers. Recent debates about standards of teacher professionalism emphasize that teachers should be able to inform and justify their professional actions and decisions on the basis of scientific evidence. Thus, sourcing is an essential competence in retrieving and using relevant research knowledge. The contributions of this special issue shed light on different processes, requirements, and consequences of sourcing in the context of teacher education and teachers' work. They study potential factors and criteria that may affect teachers' selection, evaluation, and use of (non-)scientific information sources even in the pre-service stage of their development. Moreover, the studies analyze the impact of source preferences and accessibility of scientific sources on pre-service and in-service teachers' conceptions of educational topics and perceptions of educational research knowledge. Together with the two subsequent critical discussions, the contributions of this special issue point to challenges and obstacles that research usage by teachers and its preparation in teacher education face.